Hypothyroidism has a protective causal association with hepatocellular carcinoma: A two-sample Mendelian randomization study - Lu, Likui; Wan, Bangbei; Li, Lingjun; Sun, Miao (Frontiers in Endocrinology, 2022)
Objective: Observational studies suggest an association between hypothyroidism and the risk of hepatocellular carcinoma (HCC), but the causality and direction of these effects are still inconclusive. We aim to test whether hypothyroidism is causally associated with the risk of HCC by using Mendelian randomization (MR) analysis. Methods: Single-nucleotide polymorphisms (SNPs) associated with hypothyroidism were screened via a genome-wide association study (GWAS) with 337,159 European-descent individuals. Summary-level data for HCC (372,184 individuals) were extracted from UK Biobank. An inverse-variance-weighted (IVW) method was used as the primary MR analysis. Sensitivity analyses were examined via MR-Egger regression, heterogeneity test, pleiotropy test, and leave-one-out sensitivity test. The assumption that exposure causes outcome was verified using the MR Steiger test. Results: Two-Sample MR analysis showed inverse associations between genetically predicted hypothyroidism and HCC risk (OR = 0.997, 95% CI, 0.995-0.999; P = 0.016). There were no statistical indications of heterogeneity between instruments (P-het = 0.667). Across five MR methods, genetically predicted hypothyroidism shows a consistent correlation with HCC. The leave-one-out analysis indicated that no single SNP changed the overall estimate (P = 0.016). In addition, the MR Steiger test revealed that the hypothyroidism effect on HCC was the proper causal direction (P = 0.000). Conclusion: Genetic variants predisposing to hypothyroidism were associated with lower HCC risk. Further research is required to comprehend the mechanisms underlying this putative causative association, and follow-up clinical trials need to be conducted to establish whether inducing hypothyroidism could be beneficial for HCC patients.